A path smoothing scheme for micro-line tools using cubic B-spline fitting with dominant points. Issue 1 (1st October 2022) - Hu, Yifei; Jiang, Xin; Huo, Guanying; Su, Cheng; Li, Hexiong
Abstract: To obtain higher order continuous tool path, a cubic B-spline curve fitting method is presented in this paper to process the linear tool path. First, a local cubic polynomial fitting with bidirectional scanning scheme is proposed to determine some initial dominant points. Based on these dominant points, the initial knot vector is generated by average method, and the initial B-spline is constructed. To constrain the fitting error, a Newton's method based fitting error estimation scheme and a fitting error based dominant point insertion scheme are proposed to modify the B-spline. Simulation results prove that our method can compress data and smooth tool path. Compared with another existing curve fitting method, the number of control point has decreased by 9.43%, and the machining time has decreased by 94.45% compared with traditional point-to-point (P2P) motion.